Improving Islamic Communication in Organizations to Improve Large Family Ukhuwah Abituren Musthafawiyah (Dictionary) Medan City - Delima, Wirda; Abdullah, Abdullah (LPPPIPublishing, 2025)
This journal discusses the importance of grounding Islamic communication in the Abi Turen Musthafawiyah Extended Family (KAMUS) organization in Medan City. Effective communication based on Islamic values ??is expected to strengthen brotherhood between members. Through a qualitative approach, this research analyzes existing communication practices in organizations and their impact on relationships between members. The research results show that the application of Islamic communication principles can increase the sense of brotherhood and solidarity among KAMUS members.